Practical pathway for the management of depression in the workplace: a Canadian perspective - Chokka, Pratap; Bender, Ash; Brennan, Stefan; Ahmed, Ghalib; Corbière, Marc; Dozois, David J. A.; Habert, Jeff; Harrison, John; Katzman, Martin A.; McIntyre, Roger S.; Liu, Yang S.; Nieuwenhuijsen, Karen; et al. (Frontiers in Psychiatry, 2023)
Major depressive disorder (MDD) and other mental health issues pose a substantial burden on the workforce. Approximately half a million Canadians will not be at work in any week because of a mental health disorder, and more than twice that number will work at a reduced level of productivity (presenteeism).Although it is important to determine whether work plays a role in a mental health condition, at initial presentation, patients should be diagnosed and treated per appropriate clinical guidelines. However, it is also important for patient care to determine the various causes or triggers including work-related factors. Clearly identifying the stressors associated with the mental health disorder can help clinicians to assess functional limitations, develop an appropriate care plan, and interact more effectively with worker's compensation and disability programs, as well as employers. There is currently no widely accepted tool to definitively identify MDD as work-related, but the presence of certain patient and work characteristics may help. This paper seeks to review the evidence specific to depression in the workplace, and provide practical tips to help clinicians to identify and treat work-related MDD, as well as navigate disability issues.